2015
DOI: 10.1016/j.nmni.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal ulcer promoting gene 1 (dupA1) is associated with A2147G clarithromycin-resistance mutation but not interleukin-8 secretion from gastric mucosa in Iraqi patients

Abstract: Helicobacter pylori causes peptic ulceration and gastric adenocarcinoma. The aims were to study the influence of dupA1 positivity upon interleukin-8 (IL-8) secretion from gastric mucosa and determine the prevalence of mutations responsible for clarithromycin and fluoroquinolone resistance. DNA was extracted from 74 biopsies and the virulence factors were studied. Levels of IL-8 in gastric mucosa were measured using ELISA and the mutations responsible for clarithromycin and fluoroquinolone resistance were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Unfortunately, there is no data from the North African countries regarding the polymorphism of the three region of vacA . In our study, the determined distribution is almost similar to the one determined among Sicilian and Kenyan patients [ 28 , 31 ] and differs from the others reported among European, Senegalese, Iranian, Malaysian and the South Korean ones, where vacAs1i1m1 was the most predominant genotype [ 8 , 32 34 ], while vacA s1i2m2 was the prevalent genotype in Iranian population [ 35 ]. This difference may explain the predominance of severe diseases in these regions.…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately, there is no data from the North African countries regarding the polymorphism of the three region of vacA . In our study, the determined distribution is almost similar to the one determined among Sicilian and Kenyan patients [ 28 , 31 ] and differs from the others reported among European, Senegalese, Iranian, Malaysian and the South Korean ones, where vacAs1i1m1 was the most predominant genotype [ 8 , 32 34 ], while vacA s1i2m2 was the prevalent genotype in Iranian population [ 35 ]. This difference may explain the predominance of severe diseases in these regions.…”
Section: Discussionsupporting
confidence: 77%
“…The observed discrepancy of dupA link with disease outcomes might be associate with the plasticity region of H. pylori or the limitation of PCR to detect the various forms of dupA gene; however, in order to draw a better conclusion further experiments are required[58,59]. Interestingly, the presence of dupA was significantly associated with H. pylori eradication failure with no biologic explanation[60-62]. In conclusion, it sounds that rather than promoting gastric cancer or duodenal ulceration in all populations, dupA is an effective factor for some of populations.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies with H. pylori infected patients showed that cagA , complete dupA cluster and smoking habit were associated with increased levels of IL-8 production from gastric mucosa[ 55 ]. It was also shown in another study that the high IL-8 level in gastric mucosa was neither significantly associated with dupA1 positive strains nor with dupA negative strains[ 56 ]. A significant association has also been found between dupA1 and A2147G clarithromycin resistance mutation.…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%